2011
DOI: 10.1097/acm.0b013e3182224f1f
|View full text |Cite
|
Sign up to set email alerts
|

Medical Studentsʼ Self-Reported Empathy and Simulated Patientsʼ Assessments of Student Empathy: An Analysis by Gender and Ethnicity

Abstract: A tool for SPs to assess students' empathy during an OSCE could be helpful for unmasking some deficits in empathy in students during the third year of medical school. Because the authors found no significant differences on self-reported empathy, the differences they observed in the SPs' assessments of white and Asian American students were unexpected and need further exploration. These findings call for investigation into the reasons for such differences so that OSCEs and other examinations comply with the gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 19 publications
8
52
1
2
Order By: Relevance
“…As in most other studies, we confirmed higher level of empathy in females than in males (3,4,20,25,30). The gender differences in empathy should be explained with intrinsic biological factors and also with extrinsic factors, e.g.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…As in most other studies, we confirmed higher level of empathy in females than in males (3,4,20,25,30). The gender differences in empathy should be explained with intrinsic biological factors and also with extrinsic factors, e.g.…”
Section: Discussionsupporting
confidence: 74%
“…Empathy in first-year medical students in Slovenia is similar to that in some other European countries such as Austria (18) and Portugal (19), slightly higher than in Japan (20), Iran (23) and Kuwait (29) and lower than in the United States (3,25) and Brazil (21). Cultural differences seem to have impact on the level of empathy in medical students at the beginning of their medical education (30). It seems that the emotional component of care is highly valued in America but less in Europe or in Asia.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Given the changing demographic and ethnic composition of medical students and physicians, particularly in the United States, and the emphasis placed on ethnic diversity in the medical workforce (AAMC 2004;Nickens et al 1994), it is important to control for ethnic status as a possible intervening variable in the validity studies. Our research findings suggest that ethnicity contributes significantly to the assessment of cognitive (Rosenfeld et al 1992;Veloski et al 2000) and noncognitive measures (Berg et al 2011a) in medical education research.…”
Section: (8) Volunteer Biasmentioning
confidence: 99%
“…Significant associations have been found between JSE scores on the one hand, and simulated patients' evaluations of students' empathic engagement in objective structured clinical exam stations (OSCE, Berg et al 2011aBerg et al , 2011b, peer nominations on professionalism attributes (Pohl et al 2011), and scores of attitudes toward interprofessional collaboration (Hojat et al, 2012c;Ward et al 2009), on the other hand.…”
Section: E1279mentioning
confidence: 99%